2021
DOI: 10.1088/1741-2552/abf97c
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial photobiomodulation changes topology, synchronizability, and complexity of resting state brain networks

Abstract: Objective. Transcranial photobiomodulation (tPBM) is a recently proposed non-invasive brain stimulation approach with various effects on the nervous system from the cells to the whole brain networks. Specially in the neural network level, tPBM can alter the topology and synchronizability of functional brain networks. However, the functional properties of the neural networks after tPBM are still poorly clarified. Approach. Here, we employed electroencephalography and different methods (conventional and spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 105 publications
4
24
0
Order By: Relevance
“…However, even with room for improvement of accuracy, our reported results and conclusions in this study are in good agreement with a recent fMRI-driven report, showing that increases in brain-wide FC of the human brain were observed with connections involving the stimulated hemisphere having a significantly larger increase than those in the contralateral hemisphere (Dmochowski et al, 2020). Several independent studies also confirmed that tPBM enables to stimulate electrophysiological oscillation powers and enhance functional connectivity based on whole-head electroencephalogram (Berman et al, 2017;Zomorrodi et al, 2019;Ghaderi et al, 2021).…”
Section: Potential Contamination Of Extracranial Layers To the Interp...supporting
confidence: 92%
See 2 more Smart Citations
“…However, even with room for improvement of accuracy, our reported results and conclusions in this study are in good agreement with a recent fMRI-driven report, showing that increases in brain-wide FC of the human brain were observed with connections involving the stimulated hemisphere having a significantly larger increase than those in the contralateral hemisphere (Dmochowski et al, 2020). Several independent studies also confirmed that tPBM enables to stimulate electrophysiological oscillation powers and enhance functional connectivity based on whole-head electroencephalogram (Berman et al, 2017;Zomorrodi et al, 2019;Ghaderi et al, 2021).…”
Section: Potential Contamination Of Extracranial Layers To the Interp...supporting
confidence: 92%
“…Different imaging modalities have been utilized concurrently with tPBM administration to investigate its effects on the brain, such as electroencephalography (EEG) (Wang et al, 2019;Ghaderi et al, 2021), functional magnetic resonance imaging (fMRI) (Vargas et al, 2017;Dmochowski et al, 2020), broadband near-infrared spectroscopy (bbNIRS) (Tian et al, 2016;Wang et al, 2017b;Pruitt et al, 2020;Saucedo et al, 2021), or functional near-infrared spectroscopy (fNIRS) (Holmes et al, 2019;Urquhart et al, 2020b). Among them, NIRS (both fNIRS and bbNIRS) has been considered as an effective and noninvasive tool for assessing the hemodynamic (Villringer et al, 1993;Boas and Franceschini, 2011;Quaresima et al, 2012;Boas et al, 2014;Scholkmann et al, 2014) and metabolic state of the brain (Villringer et al, 1993;Smith, 2011;Tian et al, 2016;Wang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on the mechanism of tPBM-evoked electrophysiological effects in the human brain is on its early stage with only a handful of publications ( Berman et al, 2017 ; Vargas et al, 2017 ; Zomorrodi et al, 2019 ; Ghaderi et al, 2021 ; Spera et al, 2021 ), besides ours ( Wang et al, 2017 , 2019 ), in the last 4–5 years. Most of these studies have reported alterations of electroencephalography (EEG) powers by tPBM compared to sham stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, photobiomodulation has been reported to influence the global, large scale networks of the brain ( Ghaderi et al, 2021 ). These large scale networks involve the coordination and intercommunication of a number of different regions of the cortical areas involved in the processing and integration of information that is necessary to generate a number of higher-order cognitive functions, such as perception, attention, memory and emotion.…”
Section: Photobiomodulation and Wakefulnessmentioning
confidence: 99%